Franz Kafka's 'The Castle': Postmodern discourse in contemporary Austrian literature - E.M. Shastina; G.A. Frolov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The purpose of the paper is to follow the reception of F. Kafka's “The Castle” in contemporary Austrian literature based on the following novels: “The Peaches Killers” (“Die Pfirsichtöter”, 1972) by Alfred Kolleritsch, “Among the Bieresch“ (“Bei den Bieresch”, 1979) by Klaus Hoffer, and “Into the Castle” (“Ins Schloss”, 2004) by Marianne Gruber. The attention has been focused on the writers, whose creative manner reflects the tendencies in contemporary Western European literary process – from avant-gardism (A. Kolleritsch) to postmodernism (K. Hoffer, M. Gruber). The intertextual links between the works under the consideration and F. Kafka's novel have been established. The “Kafkaesque discourse” suggests that there exist direct and inverse links between the author and the reader, the extra-textual tradition and reality. The comparative methodology has been used to reveal the mechanism of reception of the “Kafkaesque discourse” in contemporary Austrian literature, as well as to draw conclusions about the ways the authors treat ontological questions. Particular emphasis has been placed on the narrative strategies of Austrian literary avant-gardism, postmodern discourse of the second half of the 20th and the beginning of the 21st centuries, typological similarity of the analyzed novels, which seems productive for understanding of the influence of literature during the period of modernism on the emergence of a postmodern paradigm in the German-speaking literary space.